Local Product Promotional Content on President Joko Widodo’s Instagram - Wenny Maya Arlena; Mohammad Ichsan Rasyid (UIR Press, 2023)
So far, Indonesia has only been known as a big market for global products. So positioning Indonesia as a country that making domestically produced products as well as a producer country becomes a very important nation step. President Jokowi through his Instagram often promotes products that made in the country, and the domestic consumers often responded positively. This study seeks to understand how President Jokowi promoted locally made products through his Instagram. Using literature study as a data collection method, content analysis as an analytical technique, and the AIDA Model as a theoretical framework to describe how the uploaded promotional content was being rolled out. This study found that the President's promotional posts are in line with the AIDA framework, and in his posts, the president not only creates awareness and interest, but also seeks to build a sense of pride and confidence towards the locally made products and the nation production capabilities amongst the audiences, particularly the followers. From this research, researchers can further discuss the effects and how audiences interpret the promotional content of President Jokowi.